Edukacja na rzecz zrównoważonego rozwoju z duchowością w Międzynarodowej Sieci Edukacyjnej PILGRIM - Borowiec, Ewa (Studia Edukacyjne, 2025)
The article presents the functioning of the International Educational Network PILGRIM, which focuses on education for sustainable development with a spiritual, ethical and religious dimension. Established in 2002, the network unites 62 institutions in Poland and promotes educational projects through content published, among other sources, in newsletters. The author conducts an analysis of the principles of the network, the educational content, and the approach to the learning process. A fundamental component of the educational approach employed within PILGRIM is experiential learning, encompassing spiritual practices. This approach permeates the curriculum with a personal dimension and fosters the transformation of students’ attitudes. The dissemination of knowledge occurs within educational institutions and religious and interfaith communities.